2014
DOI: 10.3332/ecancer.2014.475
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection in head and neck squamous cell carcinoma

Abstract: IntroductionHuman Papillomavirus (HPV) has been associated with benign and malignant lesions in different epitheliums. The relationship between specific genotypes of high-risk HPV and some human cancers is well established. The aim of this work was to detect the HPV genotypes present in head and neck squamous cell carcinoma (HNSCC).MethodsWe evaluated 71 samples of patients with histopathological diagnosis of HNSCC. The DNA extraction was conducted with the QIAGEN commercial kit. HPV detection and genotyping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
2
9
1
1
Order By: Relevance
“…A high percentage of the samples were positive for HPV infection, which coincides with studies carried out by Veitía et al, 17 who reported that 66.7% of Venezuelan patients with head and neck tumors were positive for this virus, with the highest infection rate found in the oral cavity. Studies worldwide show similar results, for example Kreimer et al 18 suggest the oral cavity is the anatomical location with the greatest tendency to develop these kinds of tumors, also being a location with the highest rate of HPV infection.…”
supporting
confidence: 73%
“…A high percentage of the samples were positive for HPV infection, which coincides with studies carried out by Veitía et al, 17 who reported that 66.7% of Venezuelan patients with head and neck tumors were positive for this virus, with the highest infection rate found in the oral cavity. Studies worldwide show similar results, for example Kreimer et al 18 suggest the oral cavity is the anatomical location with the greatest tendency to develop these kinds of tumors, also being a location with the highest rate of HPV infection.…”
supporting
confidence: 73%
“…In relation to the anatomical location, the oral cavity appeared to have a greater HPV positivity (66.7%) compared to the oropharynx (33.3%). Our ndings are similar to those reported by Vietía et al [22].…”
Section: Discussionsupporting
confidence: 93%
“…The high incidence of high-risk HPV genotypes, especially genotypes16 and 18, have been well established and reported in several studies at all the anatomical location. (22,23). However, the role of HPVs as etiological factor for HNSCCs is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC presents primarily in males, and the age of appearance is being an important factor [ 10 , 11 ]. In this investigation, the average age was maintained within the range described of 60.34 ± 14.48 years (range 19–89), and in agreement with the previous reports, this type of malignity presents most frequently between the fifth and seventh decades of life, with a mean average of 62 ± 12 years [ 12 ].…”
Section: Discussionmentioning
confidence: 99%